MENINGKATKAN KEPEDULIAN SISWA TERHADAP LINGKUNGAN EKOSISTEM PERSAWAHAN DENGAN MODEL PENULISAN BUKU AJAR BIOLOGI SMA BERWAWASAN LOKAL DAN EKOLOGI - Achyani, Achyani (UNIVERSITAS MUHAMMADIYAH METRO, 2010)
A study using Research and Development design Â was conducted to produce a model of Biology hand book writing which is ecology and local oriented as an effort to increase studentsâ care toward environment. The background of this research is the reality which isÂ still going on so far that the awareness and care of the school graduatee toward the environement safe is still low. Besides, hard science instructional at school could not affect or intervene the graduateeâs characteristics, for instance in keeping the environment awareness. Meanwhile, there are many concepts of environment which had been taught through hard science especially biology. So in the researcherâs point of view, biology subject has strategic role to prevent or mitigate the environment disaster caused by human activities. The model was validated at rice field environments. The analysis of the research result includes three aspects, namely: 1) text comprehension, 2) environment care attitude, and 3) handbook readibility. Based on the result of rice field ecosystem data analysis, it was found that (1) there wasÂ a significant difference between experimental class and control class in the rice field ecosystem which is shown by tcalculation > ttable (6.150 > 2.00); (2) there was strong correlation between studentsâ comprehension and attitude which is shown by coeficient correlation (r) 0.769. While the text readability test (Cloze test) shown (1) the readability of rice field ecosystem text is 56,72% (moderate). Therefore, the conclusion is that all of the texts in the developed book are fit and proper for SMA students of grade X.Â Kata kunci: Penulisan buku ajar, orientasi ekologi dan lokal, kepedulian terhadap lingkungan